2005
DOI: 10.1016/j.adolescence.2005.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Are tattooing and body piercing indicators of risk‐taking behaviours among high school students?

Abstract: PurposeTo date, studies pertaining to possible links between body modification and risk‐taking behaviours have been conducted mainly among targeted groups. The objective of this study is to examine the influence of a number of risk‐taking behaviours on the probability of being pierced or tattooed among a general adolescent population.MethodsData come from a cross‐sectional study conducted among a sample of 2180 students aged 12–18. Data were collected directly from students through a self‐report survey.Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
93
1
4

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(107 citation statements)
references
References 29 publications
7
93
1
4
Order By: Relevance
“…In the present study, 8.4% of the youths had body modifications: 3.2% tattooing and 6% body piercing other than earlobes. This is the first survey regarding body modifications in Brazilian youths, and as observed by others [1,[9][10][11][12][13], we found a stricter association between body modifications and risk behaviors, highlighting these practices as a useful marker for behaviors that put individuals at risk for morbidity and mortality. Indeed, tattooed/pierced scholar adolescents reported 2.7-fold more sexual experience, 7.2-fold more drug use and 5.5-fold more alcohol consumption than those not tattooed and/or pierced.…”
supporting
confidence: 51%
See 1 more Smart Citation
“…In the present study, 8.4% of the youths had body modifications: 3.2% tattooing and 6% body piercing other than earlobes. This is the first survey regarding body modifications in Brazilian youths, and as observed by others [1,[9][10][11][12][13], we found a stricter association between body modifications and risk behaviors, highlighting these practices as a useful marker for behaviors that put individuals at risk for morbidity and mortality. Indeed, tattooed/pierced scholar adolescents reported 2.7-fold more sexual experience, 7.2-fold more drug use and 5.5-fold more alcohol consumption than those not tattooed and/or pierced.…”
supporting
confidence: 51%
“…However, investigations have appointed the risk of viral infections during these procedures [2, 3, 5, 6]. More recently these practices have also been associated with risk-taking behavior [1,7].Investigations have showed variable distribution in the body modifications prevalence in adolescents, varying from 4.5% to 29% for tattooing [1,[9][10][11][12], and 4.3% to 48% to body piercing [1,7,10,11,13,14]. In the present study, 8.4% of the youths had body modifications: 3.2% tattooing and 6% body piercing other than earlobes.…”
mentioning
confidence: 99%
“…Only 2 publications have investigated the relationship between BP and eating disorders, with mixed results [4,20] . The findings have also been less consistent with regard to the association between BP and depressive symptoms [2,3,10,15,22] as well as suicide ideation and suicide attempts [2,4,13] .…”
mentioning
confidence: 95%
“…Three large studies found that BP was related to antisocial activity in adolescents [OR = 2.6 (99% CI = 1.3-5.3) for history of truancy] [4,13,22] . Although BP was not found to be linked with the score on the Psychopathy Scale [15] , it was correlated with subclinical psychopathy, a personality construct associating impulsive thrill-seeking and callous affect [18] .…”
Section: 9)]mentioning
confidence: 99%
See 1 more Smart Citation